Childhood and the pandemic: Chronicle of an absence foretold - Ester Massó Guijarro (Instituto de Salud Colectiva, Universidad Nacional de Lanús, 2021)
As the COVID-19 pandemic has made visible, childhood is the virus's proverbial south: a world where care is not a value chosen from a place of desire, and where children's voices are silenced at the hands of an ancestral epistemic injustice. Thus, the transformation that human societies are undergoing due to COVID-19 has significantly impacted the rights of children, both at the micro and the macro levels. In Spain - a country that has been particularly hard-hit by the pandemic - we find that both infancy (especially through obstetric violence) and childhood at all its stages fall victim to an adultcentric paradigm based on control and epistemic injustice. This essay analyzes and discusses some of the negative consequences observed in this country related to the care for and the confinement of minors and their families - which has occurred as a result of the pandemic - and considers that the crisis triggered by COVID-19 may be an opportunity to shed light on situations of ancestral injustice towards children.